A functional imaging study of germinating oilseed rape seed. Issue 4 (11th August 2017) - Munz, Eberhard; Rolletschek, Hardy; Oeltze‐Jafra, Steffen; Fuchs, Johannes; Guendel, André; Neuberger, Thomas; Ortleb, Stefan; Jakob, Peter M.; Borisjuk, Ljudmilla
Summary: Germination, the process whereby a dry, quiescent seed springs to life, has been a focus of plant biologist for many years, yet the early events following water uptake, during which metabolism of the embryo is restarted, remain enigmatic. Here, the nature of the cues required for this restarting in oilseed rape ( Brassica napus ) seed has been investigated. A holistic in vivo approach was designed to display the link between the entry and allocation of water, metabolic events and structural changes occurring during germination. For this, we combined functional magnetic resonance imaging with Fourier transform infrared microscopy, fluorescence‐based respiration mapping, computer‐aided seed modeling and biochemical tools. We uncovered an endospermal lipid gap, which channels water to the radicle tip, from whence it is distributed via embryonic vasculature toward cotyledon tissues. The resumption of respiration is initiated first in the endosperm, only later spreading to the embryo. Sugar metabolism and lipid utilization are linked to the spatiotemporal sequence of tissue rehydration. Together, this imaging study provides insights into the spatial aspects of key events in oilseed rape seeds leading to germination. It demonstrates how seed architecture predetermines the pattern of water intake, which sets the stage for the orchestrated restart of life. Abstract : See also the Commentary on this article byPenfield, 216: 965–966 .